The Transformation of Land Law in Indonesia: From Commodification to Maqāṣid and Social Justice - Firman Muntaqo; Mashudi Mashudi; Alip Dian Pratama; Abdullah Rosikh Fil Ilmi; Iza Rumesten (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2025)
This article examines the transformation of Indonesian land law from the paradigm of fundamental justice embodied in the 1960 Basic Agrarian Law (UUPA) to a market-oriented framework shaped by the Omnibus Law on Job Creation and decentralization policies. This shift generates tensions between constitutional mandates, Pancasila values, customary law, and politico-economic interests that often marginalize structural justice. The study aims to analyze how these foundational values interact with Islamic legal philosophy through the maqāṣid approach to construct a more equitable and sustainable agrarian system. Employing a qualitative normative legal method combined with interpretive and comparative analysis, the research finds that a dialogical integration of UUPA principles, maqāṣid, and the social function of land can generate an alternative paradigm of land governance. The novelty lies in proposing a model emphasizing tawāzun (balance), ecological protection, and social equality. Theoretically, the article enriches global law-and-development discourse, while practically providing normative grounds for reconstructing agrarian policy toward justice and sustainability.